Маловідомий провулок на Татарці та його історичні споруди - Горькова, А.О. (Сіверщина в історії України, 2024)
Стаття присвячена результатам дослідження історичних споруд, що розташовуються на території місцевості Татарка в Києві. На сьогодні ці об’єкти не мають пам’яткоохоронного статусу і знаходяться під загрозою фізичного знищення. У статті висвітлено історію цих об’єктів, визначено їхню автентичність та ряд ознак, за якими вони пропонуються для включення до Переліку щойно виявлених об’єктів культурної спадщини міста Києва. Окреслено ряд основних проблем, з якими стикається науковець у процесі дослідження «небажаної» культурної спадщини та перспектив їхнього вирішення з метою подальшого збереження окремих будівель і споруд, що мають архітектурну та історичну цінність, та відображають характер унікальної місцини. The article is devoted to the results of the study of historical buildings that are located on the territory of the Tatarka area in Kyiv, today these objects don’t have monument protection status and are under the threat of physical destruction. At the beginning of 2024, the Shevchenko district, the territory of which included the historical area of Tatarka, counts 1,388 objects of cultural heritage, of which only 27 are located within the boundaries of Tatarka. Despite such minor indicators, which would encourage the preservation of immovable heritage of the historical place, every year new threats are appeared in the form of developers or unscrupulous owners who destroy monuments. To preserve such buildings, which became an «unwanted legacy», the city authorities introduced a moratorium on reconstruction and/or major repairs of the buildings of the 19th–20th centuries in order to prevent their destruction, thereby providing a certain time for their research and inclusion in the List of recently discovered objects of cultural heritage of the city of Kyiv. Our attention was attracted by 3 residential buildings: No. 4, 6, 12 on Delehatskyi Lane, which are the only historical buildings on it that have survived to this day. These buildings were built in the historicist style using elements of the so-called brick style and give an introduction of the traditional character of the historical environment of Tatarka. The relevance of the study is due to the need to signify historical, architectural significance of the objects located on Delehatskyi Lane, to highlight possible ways of their protection and to attract the attention of historians, monument experts, and the active public to their future fate.